Numerical Analysis of the Energy Improvement of Plastering Mortars with Phase Change Materials - A. Váz Sá; R. M. S. F. Almeida; H. Sousa; J. M. P. Q. Delgado (Advances in Materials Science and Engineering)
Building components with incorporated phase change materials (PCMs) meant to increase heat storage capacity and enable stabilization of interior buildings surface temperatures, whereby influencing the thermal comfort sensation and the stabilization of the interior ambient temperatures. The potential of advanced simulation tools to evaluate and optimize the usage of PCM in the control of indoor temperature, allowing for an improvement in the comfort conditions and/or in the cooling energy demand, was explored. This paper presents a numerical and sensitivity analysis of the enthalpy and melting temperature effect on the inside building comfort sensation potential of the plastering PCM.